Rapid long-term bone loss following stroke in a man with osteoporosis and atherosclerosis. - Poole, K; Warburton, E; Reeve, J (2005)
Bone loss in humans has been reported where there is reduced mechanical loading such as in space flight, spinal cord injury, and stroke. Whether osteoporotic patients are susceptible to further bone loss in states of underloading such as hemiparesis is unknown. Here we report the case of a 64-year-old man with established idiopathic osteoporosis and atherosclerosis who presented with a right middle cerebral artery territory stroke. Annual bone mineral density measurements were made at the left hip and spine before and after left hemiparesis. The left total hip T-score was -3.2 before the stroke. Following stroke, there was rapid and sustained bone loss with a reduction in bone mineral density (BMD) of 21.6% over 3 years despite oral bisphosphonate therapy. There was also an unexpected decline in vertebral BMD after the stroke. This is the first report of the accelerated effect of hemiplegia on bone loss in an already osteoporotic skeleton.